Envisioning Systems Engineering as a Transdisciplinary Venture. Issue 3 (14th November 2018) - Sillitto, Hillary; Martin, James; Griego, Regina; McKinney, Dorothy; Arnold, Eileen; Godfrey, Patrick; Dori, Dov; Krob, Daniel; Jackson, Scott
ABSTRACT: We envision that systems engineering can be transformed into a truly transdisciplinary discipline ‐ a foundational meta‐discipline that supports and enables collaboration between all the disciplines that should be involved in conceiving, building, using and evolving a system such that it will continue to be successful and fit for purpose as time passes. Systems engineering can be applied in different ways depending on the situation and how well current systems engineering process patterns are matched to the problem in hand. We identify four elements of this new transdisciplinary framework: systems engineering tenets; systems engineering approach; systems engineering process; and systems engineering toolbox. We suggest that the use of systems engineering then needs to be considered in three domains: problem space, solution space, and transformation space that helps us along the development‐delivery‐evolution trajectory. We propose twelve systems engineering tenets and show how they should be applied in these three domains. We perceive that even though all elements of the current systems engineering process can be justified in terms of the twelve tenets applied to these three domains, the current commonly used, standardized systems engineering process is not suitable for all situations requiring a systems engineering approach or an application of the systems engineering tenets. We claim that the framework presented in this paper can act as a unifying structure that facilitates the evolution of systems engineering from the current focus on a "standardized" process model suited to a particular class of problem, to a more agile and capable "transdiscipline" that will provide an enabling construct for more successful collaborations that can better deal with a wider range of complicated, complex and chaotic problem situations.